Efektivitas Pengunaan QRIS Meningkatkan Perkembangan UMKM di Universitas Sultan Ageng Tirtayasa - Vera Maria; Yona Maydiana (Journal Economic Excellence Ibnu Sina, 2025)
This study aims to analyze the effectiveness of the use of the Quick Response Code Indonesian Standard (QRIS) to improve the efficiency of Micro, Small and Medium Enterprises (MSMEs) transactions to make them safer and easier to access in the Sultan Ageng Tirtayasa University, Sindangsari environment. QRIS is one of the payment instruments introduced by Bank Indonesia. This study uses a qualitative method on MSMEs that actively use QRIS in the payment method available at the Sultan Ageng Tirtayasa University canteen, Sindangsari. This data was collected through observation and interviews with 7 MSME owners and 10 buyers, to find out the reasons for choosing non-cash over cash, to find out the increase in the number of transactions after using QRIS, the advantages of using QRIS and its obstacles as well as the positive and negative impacts on the effectiveness and operations of MSMEs. Thus, QRIS has proven effective as a digital payment instrument that supports the growth of MSMEs at Sultan Ageng Tirtayasa University, Sindangsari.